miR-301a as an NF-κB activator in pancreatic cancer cells - Lu, Zhongxin (Nature Publishing Group, 2011)
NF-κB is constitutively activated in most human pancreatic adenocarcinoma, which is a deadly malignancy with a 5-year survival rate of about 5%. In this work, we investigate whether microRNAs (miRNAs) contribute to NF-κB activation in pancreatic cancer. We demonstrate that miR-301a down-regulates NF-κB-repressing factor (Nkrf) and elevates NF-κB activation. As NF-κB promotes the transcription of miR-301a, our results support a positive feedback loop as a mechanism for persistent NF-κB activation, in which miR-301a represses Nkrf to elevate NF-κB activity, which in turn promotes miR-301a transcription. Nkrf was found down-regulated and miR-301a up-regulated in human pancreatic adenocarcinoma tissues. Moreover, miR-301a inhibition or Nkrf up-regulation in pancreatic cancer cells led to reduced NF-κB target gene expression and attenuated xenograft tumour growth, indicating that miR-301a overexpression contributes to NF-κB activation. Revealing this novel mechanism of NF-κB activation by an miRNA offers new avenues for therapeutic interventions against pancreatic cancer.